2020
DOI: 10.46542/pe.2020.201.273281
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing choice of career: A comparative study among medical, dental and pharmacy students in a private university in Malaysia

Abstract: Background: Students choose their careers based on many factors, which vary for every country. Recent advancements in healthcare systems have made pharmacy one of the most pursued professions. Aim: To study the factors that influence students in Malaysia to choose pharmacy as their career. Methods: A cross-sectional study was conducted among first-year medicine, dentistry and pharmacy students in a private university in Malaysia. One-way analysis of variance followed by Tukey’s post-hoc test was used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The final category covers education related factors including good science background, role models etc. One or more factors from these categories have been reported as influencing choice of pharmacy by students all over the world (Hasan et al, 2010;Shen et al, 2014;Beedemariam et al, 2014;James et al, 2018;Al-Qudah et al, 2019;Alshehri et al, 2021;Isah et al, 2021;Sajjad et al, 2021). The most highly rated factors by respondents in this study largely fell within the first two groups (career/work related and intrinsic factors).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The final category covers education related factors including good science background, role models etc. One or more factors from these categories have been reported as influencing choice of pharmacy by students all over the world (Hasan et al, 2010;Shen et al, 2014;Beedemariam et al, 2014;James et al, 2018;Al-Qudah et al, 2019;Alshehri et al, 2021;Isah et al, 2021;Sajjad et al, 2021). The most highly rated factors by respondents in this study largely fell within the first two groups (career/work related and intrinsic factors).…”
Section: Discussionmentioning
confidence: 76%
“…These options could include careers in hospital pharmacy, community pharmacy, industrial pharmacy, veterinary pharmacy and so on. Several studies have been carried out in many countries to assess career options and the factors affecting these choices among pharmacy students (Hasan et al, 2010;Ubaka et al, 2013;Shakeel et al, 2013;Salman et al, 2013;Loo et al, 2017;James et al, 2018;Alhomoud et al, 2019;Al-Qudah et al, 2019;Jarab et al, 2021). As would be expected, most of these studies have reported varying results (both for career choices and the factors influencing these choices).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivations for studying dentistry ranged from the desire to be capable of helping others [36,37], achieving self-esteem and interests related to health care, but also the chance to have a well-paid prestigious position are reasons for choosing the dental profession [36,37]. Moreover, personal and family background, work-life balance [38], professional/social status [39,40], job security, flexible work hours [39], professional independence [37], intellectual challenges, security, recommendation by others, and non-admission to other degree programs [37] play a role in the choice, with data on sex, ethnicity, mode of entry into college [41], parental education, and marital status [37]. Some underlying factors also influenced the career choice as professional work environment, health care, etc.…”
Section: Influence and Motives On The Choice Of Professionmentioning
confidence: 99%